Nested Tests of Alternative Term-Structure Theories - Kane, Edward J. (The Review of Economics and Statistics, 1983)
Controversies in term-structure theory center around the existence and variability of term premia in securities yields. In this paper, the term premium on a default-free n-period bond is defined as the difference between its observable yield to maturity and the average expected per-annum rate of return on an n-period strip of rollover investments in one-period bonds. To test alternative term-structure theories without introducing ex post proxies for expectational variables, this paper uses a set of cross-section interest- rate forecasts collected jointly with Burton Malkiel of Princeton University from a population of large institutional lenders at four different phases of a single interest-rate cycle. Statistical tests strongly confirm the existence of nonzero term premia at each survey date, thereby rejecting the pureexpectations theory of the term structure. Additional tests are unable to reject restrictions implied by the liquidity-premium hypothesis that term premia should be positive and increase with maturity. Finally, contrary to the martingale hypothesis, ex ante term-premium data vary significantly over time and show a positive association with the level of interest rates.